2014
DOI: 10.1063/1.4896728
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy-oxygen defects in p-type Si1−xGex

Abstract: Oxygen-vacancy defects and in particular the VO pairs (known as A-centers) are common defects in silicon (Si) with a deleterious impact upon its properties. Although oxygenvacancy defects have been extensively studied in Si there is far less information about their properties in p-type doped silicon germanium (Si 1-x Ge x ). Here we use Fourier transform infrared spectroscopy (FTIR) to determine the production and evolution of oxygen-vacancy defects in p-type Si 1-x Ge x . It was determined that the increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(47 reference statements)
2
1
0
Order By: Relevance
“…2a, with the prior RTP at 1250°C, the Cz-Si 1-x Ge x specimen has lower Au s concentration than the Cz-Si counterpart. Accordingly, it is derived that the formation of VO m complexes during the RTP at 1250°C is to a certain extent suppressed in CzSi 1-x Ge x in comparison with that in Cz-Si, which is in agreement with the previous theoretical calculation and experiment results obtained for the electron-irradiated Si 1-x Ge x [15,16,[30][31][32][33]. The reason for the suppressed formation of VO m complexes in Cz-Si 1-x Ge x will be explored later.…”
Section: Evaluation Of Rtp-induced Vo M Complexessupporting
confidence: 85%
See 1 more Smart Citation
“…2a, with the prior RTP at 1250°C, the Cz-Si 1-x Ge x specimen has lower Au s concentration than the Cz-Si counterpart. Accordingly, it is derived that the formation of VO m complexes during the RTP at 1250°C is to a certain extent suppressed in CzSi 1-x Ge x in comparison with that in Cz-Si, which is in agreement with the previous theoretical calculation and experiment results obtained for the electron-irradiated Si 1-x Ge x [15,16,[30][31][32][33]. The reason for the suppressed formation of VO m complexes in Cz-Si 1-x Ge x will be explored later.…”
Section: Evaluation Of Rtp-induced Vo M Complexessupporting
confidence: 85%
“…Markevich et al [14] have found at least three configurations of V-O complexes with distinct levels in Cz-Si 1-x Ge x , among which the most stable configuration consists of a Si-O-Si unit and a Ge-Si reconstructed bond in a vacancy. Sgourou et al [15,16] found that both the VO production and the VO annealing temperature were reduced and, moreover, the conversion of VO into VO 2 is suppressed in Cz-Si 1-x Ge x with respect to the case of Cz-Si. By comparison, the formation of V-O complexes in Cz-Si 1-x Ge x during the high temperature RTP has hardly been investigated so far.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, the VO 2 band is largerly suppressed in the latter sample. Interestingly, the suppression of the VO 2 band due to Pb doping (with [Pb] = 10 18 cm -1 ) is almost the same with the suppression of VO 2 in n-type and p-type Si 1-x Ge x material [32,33] with x = 5.6 % that is with Ge content at least three orders of magnitude larger than that of Pb. Figure 3 shows the production of the VO, C i O i and C i C s / C i O i versus covalent radius of the isovalent dopant.…”
Section: Resultssupporting
confidence: 53%